2013
DOI: 10.1371/journal.pone.0070536
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling (SOCS) 5 Utilises Distinct Domains for Regulation of JAK1 and Interaction with the Adaptor Protein Shc-1

Abstract: Suppressor of Cytokine Signaling (SOCS)5 is thought to act as a tumour suppressor through negative regulation of JAK/STAT and epidermal growth factor (EGF) signaling. However, the mechanism/s by which SOCS5 acts on these two distinct pathways is unclear. We show for the first time that SOCS5 can interact directly with JAK via a unique, conserved region in its N-terminus, which we have termed the JAK interaction region (JIR). Co-expression of SOCS5 was able to specifically reduce JAK1 and JAK2 (but not JAK3 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 64 publications
0
63
0
1
Order By: Relevance
“…In addition to regulating degradation of the EGFR, SOCS5 also accelerates degradation of ErbB2 and ErbB4 [59]. Furthermore, SOCS5 associates following growth factor stimulation with Shc1 at pY317 through its SH2 domain [62] suggesting that SOCS5 not only limits receptor stability but also induces degradation of downstream signaling proteins. SOCS5 also weakly associates with KIT but its role in KIT regulation has not been studied [18].…”
Section: Socs5mentioning
confidence: 99%
“…In addition to regulating degradation of the EGFR, SOCS5 also accelerates degradation of ErbB2 and ErbB4 [59]. Furthermore, SOCS5 associates following growth factor stimulation with Shc1 at pY317 through its SH2 domain [62] suggesting that SOCS5 not only limits receptor stability but also induces degradation of downstream signaling proteins. SOCS5 also weakly associates with KIT but its role in KIT regulation has not been studied [18].…”
Section: Socs5mentioning
confidence: 99%
“…4 The function of SOCS5 is not yet clear, but it is thought to act as a tumor suppressor and was shown previously to act as an inhibitor of janus kinase/signal transducer and activation of transcription pathways in endothelial cells. 13 Here, Loyer et al 4 show that inhibition of SOCS5 by siRNA increases monocyte chemoattractant protein-1 and interleukin-6 release without affecting KLF2, KLF4, and NOS3 levels, indicating that SOCS5 indeed directly protects against endothelial activation and inflammation. In which stages of atherosclerosis development the miR-92a-SOCS5 pathway plays its most prominent role still warrants further investigation.…”
Section: Circulation Researchmentioning
confidence: 88%
“…6 We also demonstrated that SOCS5 could bind all four JAK family members, although it was found to selectively inhibit only JAK1 and JAK2 autophosphorylation, and this function was dependent on the SOCS5 N-terminal region. 22 The conserved N-terminal region in SOCS5 (SOCS5 175-244 ) facilitates a direct interaction with the kinase domain of JAK and has therefore been designated the JAK interaction region (JIR). 22 The equilibrium dissociation constant (K D ) for the interaction of SOCS5 JIR with the kinase domain of JAK1 was found to be 0.5 µM.…”
Section: Introductionmentioning
confidence: 99%
“…22 The conserved N-terminal region in SOCS5 (SOCS5 175-244 ) facilitates a direct interaction with the kinase domain of JAK and has therefore been designated the JAK interaction region (JIR). 22 The equilibrium dissociation constant (K D ) for the interaction of SOCS5 JIR with the kinase domain of JAK1 was found to be 0.5 µM. 22 Deletion of the JIR impaired the ability of SOCS5 to inhibit IL-4 induced STAT6 activity, suggesting that this region was functionally important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation